Exploring Genetic Variability of the Partial Kappa-Casein Gene in Nili-Ravi Buffalo and Sahiwal Cattle of Pakistan - Riaz, Muhammad Naeem; Mehmood, Sarfraz; Siddique, Abubakar; Akhtar, Hafiz Muhammad Bilal; Jamil, Khansa; Jamil, Aatka; Kolhi, Jai Parkash; Ali, Ghulam Muhammad (Journal of Agriculture and Veterinary Science, 2024)
Recent years have seen an immense spike in scientific interest in the ҡ-CN gene polymorphism because of its strong correlation with the characteristics and composition of milk. It also plays an important role in milch breed characterization and processing properties. In the current study, two breeds of Pakistan, i.e., Nili-Ravi buffalo (n= 45) and Sahiwal (n= 60), were genotyped for the ҡ-CN gene polymorphism using PCR-RFLP. Animals of Nili-Ravi buffalo were found homozygous, showing BB genotype, while genotypes AA & AB were observed in Sahiwal cattle with the genotypic frequencies 0.6 and 0.4, respectively. Sequence analysis of Nili-Ravi buffalo samples with already published sequences of the same breed has shown two SNPs with no effect on protein functionality. However, on sequence comparison with Indian Murrah buffalo replacing Threonine with Isoleucine at codon 136, which affects protein functionality, also confirmed through PROVEAN. Moreover, in Sahiwal cattle, both synonymous as well as non-synonymous substitutions were found. This work paves the door for future studies to characterize breeds and identify unique SNPs within the breed
Keywords: Kappa-casein; Nili-Ravi Buffalo; Sahiwal cattle; SNP